ANALISIS KEUNTUNGAN USAHA RUMAH KAYU CV TUMOU PRATAMA DI KELURAHAN WOLOAN 1 KECAMATAN TOMOHON BARAT - Andrey Dymitri Makawekes; Grace Adonia Josefina Rumagit; Celcius ., Talumingan (AGRI-SOSIOEKONOMI, 2019)
This study aims to analyze the profits of CV Tumou Pratama's wooden house business in Woloan 1 Village, Tomohon Barat District. This research was conducted for 3 months, starting from September to November 2018. The data used are primary data and secondary data. Primary data was obtained from direct interviews with wood house business owner CV Tumou Pratama (one person). While secondary data was obtained from several sources are the Central Bureau of Statistics, books available at local bookstores and the internet such as google cendikia to access articles from various scientific journals and theses from other universities related to the topic of this research, especially concerning profit analysis. The results of the study indicate that CV Tumou Pratama's wooden house business during the period January 2017 to December 2018 is profitable, both in total and based on type and size (m2). The highest profit per m2 is Rp. 1,003,554, - obtained from Medium Type Wooden Houses (70 m2) compared to Small Type Wooden Houses (36 m2) of Rp.978,099; Large Type (112 m2) of Rp.698,074, -; and Extra Type (198 m2) of Rp.576.352.- *jnkd+eprm*